Comparison Of Sharia Performance And Conventional Mutual Funds In Forming Optimal Portfolio - Rika Juwita; Ruslan Abdul Ghofur; Erike Anggraini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This research aims to analyze the differences in the performance of Islamic stock mutual funds and conventional stock mutual funds in forming an optimal portfolio using the Sharpe and Treynor models. Purposive sampling was used in determining the data sample which was then analyzed using the descriptive method with a comparative study during the period January 2018 to December 2019. Hypothesis testing used a different test to determine the difference between the two using the SPSS Application Tool. The results showed that the calculation of the performance of stock mutual funds using the Sharpe method, both Islamic and conventional stock mutual funds, there was no significant difference. Likewise, the results of the calculation of the performance of stock mutual funds using the Treynor method show that there is no difference between the performance of Islamic stock mutual funds and conventional stock mutual funds. This is one proof of the development of the Islamic economy in Indonesia, especially in the capital market, so that Islamic mutual funds can compete with conventional mutual funds.